2022
DOI: 10.1007/s00248-022-02002-y
|View full text |Cite
|
Sign up to set email alerts
|

Captive Breeding and Trichomonas gallinae Alter the Oral Microbiome of Bonelli’s Eagle Chicks

Abstract: Bonelli’s eagle (Aquila fasciata) is an endangered raptor species in Europe, and trichomonosis is one of the menaces affecting chicks at nest. In this paper, we attempt to describe the oral microbiome of Bonelli’s eagle nestlings and evaluate the influence of several factors, such as captivity breeding, Trichomonas gallinae infection, and the presence of lesions at the oropharynx. The core oral microbiome of Bonelli’s eagle is composed of Firmicutes, Bacteroidota, Fusobacteria and Proteobacteria as the most ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Captivity plays a fundamental role in influencing the oral and intestinal microbiome of hosted birds of prey and is also associated with high rates of antibiotic resistance, compared to free-living birds [ 38 ]. This change can already occur after a month of direct contact between animals and humans, and the diet, especially if based on raw food, represents the first determining causal factor [ 39 , 40 , 41 ]. Some studies have shown that birds of prey fed poultry meat develop a wider range of Gram-negative bacterial flora [ 38 ]; in particular, a study on falcons has shown that the diets most commonly fed to these birds increase the levels of Salmonella in the intestinal flora [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Captivity plays a fundamental role in influencing the oral and intestinal microbiome of hosted birds of prey and is also associated with high rates of antibiotic resistance, compared to free-living birds [ 38 ]. This change can already occur after a month of direct contact between animals and humans, and the diet, especially if based on raw food, represents the first determining causal factor [ 39 , 40 , 41 ]. Some studies have shown that birds of prey fed poultry meat develop a wider range of Gram-negative bacterial flora [ 38 ]; in particular, a study on falcons has shown that the diets most commonly fed to these birds increase the levels of Salmonella in the intestinal flora [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Captivity is presently known to affect gut and oral microbiome diversity in birds of prey when compared to their wild counterparts, with observable changes within just one month of direct human contact, and diet is being pointed to as the main factor responsible for alterations in the oral microbiome [ 60 , 61 , 62 , 63 , 64 , 65 ]. For example, studies have shown that birds who are fed chicken are linked to a wider diversity of Gram-negative bacteria [ 66 ], and that the diet commonly provided to captive animals increases the levels of Salmonella in falcons [ 65 ].…”
Section: Bacteria Found In Captive Birds Of Preymentioning
confidence: 99%
“… Some variables suspected to alter the microbiome of birds of prey in captivity: contact with wildlife; direct contact with human and animal waste; contact with synanthropic species; contact with domestic waterfowl; contact with other pet birds; diet; and previous exposure to antibiotics. Based on [ 25 , 27 , 32 , 33 , 34 , 35 , 36 , 60 , 61 , 62 , 63 , 64 , 65 ] and created using BioRender ( ). …”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Most avian studies have focused on the gut microbiome; therefore, limited information is known about other body parts (Grond et al., 2018; Ross et al., 2019). Thus far, the oral microbiome, another essential community for bird species, has only been reported in a few species (Alba et al., 2023; Kropáčková et al., 2017; Schmiedová et al., 2023; Taylor et al., 2019). Microbiomes in the brood patches, uropygial glands and feathers have been reported in a few avian species, most of which occur at two or more skin locations (Grieves et al., 2021; Leclaire et al., 2019; Pearce et al., 2017; van Veelen et al., 2017; Videvall et al., 2021).…”
Section: Introductionmentioning
confidence: 99%